Women with prolonged nausea in pregnancy have increased risk for depressive symptoms postpartum - Iliadis, Stavros I. (Sci Rep, 2018)
The aim of this population-based, longitudinal study was to assess the association between nausea and vomiting in pregnancy (NVP) and perinatal depressive symptoms. Pregnant women (N = 4239) undergoing routine ultrasound at gestational week (GW) 17 self-reported on NVP and were divided into those without nausea (G0), early (≤17 GW) nausea without medication (G1), early nausea with medication (G2), and prolonged (>17 GW) nausea (G3). The Edinburgh Postnatal Depression Scale at GW 17 and 32 (cut-off ≥13) and at six weeks postpartum (cut-off ≥12) was used to assess depressive symptoms. Main outcome measures were depressive symptoms at GW 32 and at six weeks postpartum. NVP was experienced by 80.7%. The unadjusted logistic regression showed a positive association between all three nausea groups and depressive symptoms at all time-points. After adjustment, significant associations with postpartum depressive symptoms remained for G3, compared to G0 (aOR = 1.66; 95% CI 1.1–2.52). After excluding women with history of depression, only the G3 group was at higher odds for postpartum depressive symptoms (aOR = 2.26; 95% CI 1.04–4.92). In conclusion, women with prolonged nausea have increased risk of depressive symptoms at six weeks postpartum, regardless of history of depression.